ESSENTIAL HEALTHY SCHOOL ENVIRONMENT STANDARDS TO MAINTAIN CONDUCIVE LEARNING ATMOSPHERE - Wayan Maba (Bajang Institute, 2022)
The school environment is one unit of the physical, mental and social environment of the school that meets the health requirements so that it can support the teaching and learning process properly and support the growth and development process of students optimally. A healthy school environment can be realized or maintained by involving all components of the school stakeholders. This study made use of a qualitative research design with descriptive analysis. Data were collected by conducting field studies, direct observation, and interviews with school stakeholders. This study found that to maintain school health, the essential healthy standards should be carefully and intensively implemented at schools. Therefore, this research implies that schools should maintain a healthy school environment so that students can study well and comfortably.